The Role of the Ma'had Student Executive Board (Tema) in Cultivating the Passion for Intensive Learning of UNIA Prenduan Students - Rahmawati Rahmawati; Moh Nasir (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
Education is a deliberate and planned effort to develop the potential of students, including university students who are required to have a learning spirit or enthusiasm in order to achieve academic success. The learning spirit plays an important role in determining the quality of learning. In the context of education based on Islamic boarding schools, the Boarding School Student Executive Council (BEMA) at UNIA Prenduan plays an important role in cultivating the learning spirit of students. This study purposes to determine the role of the Boarding School Student Executive Council (BEMA) in cultivating the learning spirit of students at UNIA Prenduan and to identify the supporting and inhibiting factors that the BEMA supervisor in cultivating the learning spirit of students at UNIA Prenduan. This research uses a descriptive qualitative method with a case study type. The data collection techniques used are interviews, observations, and documentation. The subjects of this study are the intensive students at UNIA Prenduan, including the BEMA supervisor and several students in the second and fourth semesters. The data analysis in this study uses the Miles & Huberman model, which includes data reduction, data presentation, and drawing conclusions. The data validity in this study is checked using technique triangulation and source triangulation. The results of this study indicate that the role of the BEMA supervisor in cultivating the learning spirit of the students at UNIA Prenduan includes acting as a supervisor, motivator, manager, role model (uswatun hasanah), and facilitator. Supporting factors include the awareness and willingness of students to learn, student participation, and the availability of adequate facilities and infrastructure. In contrast, inhibiting factors include some students undermining the management, lack of skills among the management, dominance of laziness, lack of awareness among some management and students, and time management issues.